PENGARUH EKSPERIMEN INDUKSI ELEKTROMAGNETIK TERHADAP PERKEMBANGAN KREATIVITAS SISWA - Anton Winarto; Sutikno Sutikno; Masturi Masturi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims: to determine the effect of electromagnetic induction experiment in creativity that uses simple ingredients that are easily found in everyday environments, and to know the students who have high creativity and the students who have low creativity. The method used is a method of pre-experimental design with one-shot case study design study. The subjects of the study consisted of one class by the number of students in class XI 25 SMK Shipping Akpelni. Data were collected using an instrument of learning keterlaksanaan observation sheet and questionnaire (questionnaire). Keterlaksanaan learning by experimentation by students with electromagnetic induction material has been done from the beginning to the end with an average score of 88.8 and a very good response to the electromagnetic induction experiment method well known based on the questionnaire and from observations by researchers with the percentage of students who answer yes are on average 82.5%. Based on the data analysis of the results showed that learning with the experimental method of electromagnetic induction material can influence the development of students' creativity. Keywords: experiment; Electromagnetic induction; creativity.